A meta‐analysis of the effects of global warming on rice and wheat yields in a rice–wheat rotation system. (17th July 2021) - Zhou, Yongjin; Xu, Le; Xu, Youzun; Xi, Min; Tu, Debao; Chen, Jinhua; Wu, Wenge
Abstract: The effects of global warming on crop production have received great attention in recent years. However, inconsistent results have been obtained with regard to major crops such as rice and wheat in rice–wheat rotation systems of China. Therefore, we undertook a comprehensive meta‐analysis of literature data. The yield response to warming differed for rice and wheat in the rice–wheat rotation system. Overall, warming significantly increased wheat yield (by 4.8%) but significantly reduced rice yield (by 14.8%). A number of factors were responsible for these observations. For example, rice yield responses varied with the temperature increase, variety and nitrogen (N) rate. Of these, N was the most important variable influencing yield responses to warming. The yield loss for rice was lower at temperature increases of 0.40–1.40°C and at a high N rate than that at temperature increases of 1.60–2.49°C and at a low N rate, respectively. The yield loss of indica rice was lower than that of japonica rice. For wheat, however, yield responses to warming varied with the warming regime, ambient temperature, temperature increases, and CO2 concentrations. Of these factors, ambient temperature was the most important variable influencing yield in response to warming. Warming increased wheat yield at a mean growth season temperature ≤10°C, temperature increases of 0.80–1.50°C, and at ambient CO2 concentrations. In addition, either daytime warming or nighttime warming significantly increased wheat yield. However, all‐day warming had no effect on wheat yields. We conclude that global warming will benefit wheat production but result in a serious loss of rice yield in rice–wheat rotations in China. Abstract : The yield response to warming differed for rice and wheat in the rice‐wheat rotation system. Overall, warming significantly increased wheat yield (by 4.8%) but significantly reduced rice yield (by 14.8%). For rice, yield responses to warming varied with the temperature increase, variety and nitrogen rate. For wheat, however, yield responses to warming varied with the warming regime, ambient temperature, temperature increases and CO2 concentrations.